2021
DOI: 10.1186/s12913-021-06969-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a proactive referral tool for child healthcare professionals to encourage and facilitate parental smoking cessation in the Netherlands: a mixed-methods study

Abstract: Background Recently, the parent-tailored telephone based smoking cessation counseling program ‘Smoke-free Parents’ was shown to be effective in helping parents to quit smoking. To implement this program in child healthcare settings in the Netherlands, the research team developed a proactive referral tool to refer parents to Smoke-free Parents. The aim of the present implementation study was to explore the facilitators, barriers, and suggestions for improvement in the implementation of this refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[22][23][24][25] In pediatric settings, CDS systems have shown potential to support screening for SHS exposure and facilitate the connection to and delivery of evidence-based tobacco treatments. [26][27][28][29][30][31] These systems, however, have not been widely integrated into pediatric settings due to critical pediatric EHR workflow limitations, especially the inability to account for the family aspect of child health care. 32,33 EHR vendors often develop technological services for the physician-adult patient dyad and are unable to connect family relationships, making it difficult to leverage existing technologies to support care for parents through pediatric settings.…”
Section: Background and Significancementioning
confidence: 99%
“…[22][23][24][25] In pediatric settings, CDS systems have shown potential to support screening for SHS exposure and facilitate the connection to and delivery of evidence-based tobacco treatments. [26][27][28][29][30][31] These systems, however, have not been widely integrated into pediatric settings due to critical pediatric EHR workflow limitations, especially the inability to account for the family aspect of child health care. 32,33 EHR vendors often develop technological services for the physician-adult patient dyad and are unable to connect family relationships, making it difficult to leverage existing technologies to support care for parents through pediatric settings.…”
Section: Background and Significancementioning
confidence: 99%
“…18 In pediatric settings, CDS systems, including those developed by members of this study team, have shown potential in helping pediatricians screen for SHS exposure, provide treatment, and similarly increase Quitline enrollment. 19 20 21 22 23 24 25 Workflow limitations, however, have prevented their full incorporation into routine clinical practice. For CDS systems to be effective, the interface needs to be designed with the needs of parents and clinicians taken into consideration.…”
Section: Background and Significancementioning
confidence: 99%